Implementation of maternal guidelines to reduce preventable intra-partum death at a selected public hospital in Gauteng - Isabel, Coetzee-Prinsloo (University of Pretoria, 2024)
Thesis (PhD(Nursing Science))--University of Pretoria, 2023.